Perancangan Buku Ilustrasi Sebagai Sarana Pengenalan Jajanan Tradisional Jawa - Lisa Novena Tjukipto (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2022)
Over time, the existence of traditional Indonesian food has become increasingly rare due to the entry of confectionary culture from abroad so efforts are needed to remind the younger generation that traditional cuisine is important. This design aims to produce illustrated books that are able to introduce traditional Javanese snacks and attract the interest of readers aged 17-35 years. The method used is a qualitative method, through literature study and secondary data collection online. The concept used is a digital illustration with naturalist style followed by doodle illustrations. In addition, this book is equipped with making recipes so that readers can make their own snacks in this book. From this design produced the main media in the form of a 60-page illustrated book with illustrations of 13 types of traditional Javanese snacks along with their descriptions and recipes, exhibition supporting media in the form of x-banners and 3 illustrated posters, and merchandise in the form of totebags, aprons, and placemat.